Optimal Energy Taxes and Subsidies under a Cost-Effective Unilateral Climate Policy: Addressing Carbon Leakage - Peter Kjær Kruse-Andersen; Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze how a country pursuing a unilateral climate policy may contribute to a reduction in global CO2 emissions in a cost-effective way. To do so its system of energy taxes and subsidies must account for leakage of emissions from the domestic to the foreign economy. We focus on leakage occurring via international trade in electricity and via shifts between domestic and foreign production of other goods. The optimal tax-subsidy scheme is based on an intuitive principle: Impose a uniform carbon tax on all additions to global emissions caused by changes in domestic production and consumption of energy, including additions to emissions occurring via shifts in international trade. Emissions from the sector exposed to foreign competition should be taxed at reduced rates to avoid excessive carbon leakage, and a part of the carbon tax on electricity should be levied at the consumer rather than the producer level to ensure taxation of the carbon content of imported electricity. Producers of renewables-based electricity should receive a subsidy to internalize their contribution to the reduction of global emissions. In other sectors emissions should be taxed at a uniform rate corresponding to the marginal social cost of meeting the target for emissions reduction. Simulations calibrated to data for the Danish economy suggest that redesigning energy taxes and subsidies to account for carbon leakage can generate a welfare gain.
Keywords: H21; H23; Q48; Q54; 330; optimal unilateral climate policy; carbon leakage; optimal energy taxes and subsidies